Challenges Experienced by Older People During the Initial Months of the COVID-19 Pandemic - Heid, Allison R (Gerontologist, 2020)
BACKGROUND AND OBJECTIVES: The coronavirus disease 2019 (COVID-19) pandemic has created unique stressors for older people to manage. Informed by the Stress Process Model and the Transactional Model of Stress and Coping, we examined the extent to which older people are adhering to physical distancing mandates and the pandemic-related experiences that older people find most challenging. RESEARCH DESIGN AND METHODS: From May 4 to May 17, 2020, a web-based questionnaire focused on the COVID-19 pandemic was completed by 1,272 people (aged 64 and older) who were part of an ongoing research panel in New Jersey recruited in 2006. Frequencies for endorsement of physical distancing behaviors were tabulated, and open-ended responses to the biggest challenge of the pandemic were systematically coded and classified using content analysis. RESULTS: More than 70% of participants reported adhering to physical distancing behaviors. Experiences appraised as most difficult by participants fell into 8 domains: Social Relationships, Activity Restrictions, Psychological, Health, Financial, Global Environment, Death, and Home Care. The most frequently appraised challenges were constraints on social interactions (42.4%) and restrictions on activity (30.9%). DISCUSSION AND IMPLICATIONS: In the initial weeks of the pandemic, the majority of older adults reported adhering to COVID-19 physical distancing mandates and identified a range of challenging experiences. Results highlight the factors having the greatest impact on older adults, informing quantitative modeling for testing the impact of the pandemic on health and well-being outcomes, and identifying how intervention efforts may be targeted to maximize the quality of life of older adults.